A Rare Case of Near Complete Regression of a Large Cervical Disc Herniation without Any Intervention Demonstrated on MRI - Parag Suresh Mahajan; Nawal M. Al Moosawi; Islam Ali Hasan (Case Reports in Radiology)
There are very few reported cases of regression of large cervical disc herniation without any intervention—the so-called spontaneous regression, demonstrated using MRI. We report a rare and interesting case of MRI that demonstrated near complete regression of a large herniated cervical intervertebral disc, without any surgical treatment.